Earnings Management Moderates the Relationship between Green Accounting and Financial Distress on Financial Performance - NapisahNapisah; Fina Fitriyana; JulianaJuliana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Green accounting procedures have been adopted by numerous companies in response to the growing global focus on environmental responsibility. Nonetheless, monetary instability is still a major obstacle that can reduce productivity in Indonesia's manufacturing sector. The purpose of this research is to analyze industrial businesses listed on the Indonesia Stock Exchange from 2019 to 2023 and see how green accounting, financial crisis, and earnings management affect financial performance. The population in this study consists of 68 industrial sector companies, with a sample of 7 companies selected through purposive sampling based on 4 criteria. We used EViews software and Moderated Regression Analysis (MRA) for a quantitative approach. First, financial distress has a significant impact on financial performance. Second, green accounting has a significant positive effect on financial performance. Third, earnings management does not moderate the relationship between financial distress and financial performance. Fourth, earnings management does not moderate the relationship between green accounting and financial performance. With an Adjusted R-Square value of 79.73%, the study model has a high level of explanatory power. It may be used to explain the majority of the variation in financial performance. This shows that the constructed model is applicable and fits the empirical data well. Transparent reporting and real sustainability initiatives are still vital for improving company results, according to these results, as profits management methods do not change the impact of environmental and financial variables, which are important drivers of performance.